UPAYA DALAM MENINGKATKAN KECERDASAN LOGIS MATEMATIS PADA PENGENALAN LAMBANG BILANGAN MELALUI MEDIA KANCING GEMERINCING PADA ANAK USIA 3-4 TAHUN DI KB/TK TRISULA 01 PERWARI SINGOSARI - Roihatul Hasanah; Ika Ratih Sulistiani; Eko Setiawan (UNISMA, 2021)
This study aims to analyze the initial condition of children recognizing number symbols, describe how to apply rattling buttons media and analyze teacher barriers in applying rattling buttons media to improve logical mathematical intelligence in introducing number symbols to children aged 3-4 years in KB/TK Trisula 01 Perwari . The method used in this research is a qualitative approach with a case study type. The research subjects were children aged 3-4 years, class teachers, and guardians of students. The primary data of this study were obtained through in-depth interviews followed by observation and documentation as a process for analysis. The location of the institution is on Jl. Ronggolawe No. 11 Rt 07 Rw. 03 Pagentan Kec. Singosari Kab. Malang. The conclusions in this case are (1) the initial condition of children recognizing number symbols in children aged 3-4 years or KB in KB/TK Trisula 01 Perwari Singosari, namely developing according to age but not being stimulated to the maximum. (2) how to apply the jingle button media as an interesting learning medium. (3) the obstacles experienced by the teacher when applying the jingling button media are the limited number of media and the number of children, then when learning is done online this obstacle lies in the teacher who cannot directly supervise the child's development and the lack of attention by parents.